HOMO OECONOMICUS: CONCEPTUAL ASPECTS BETWEEN DILEMMAS AND PARADOXES - Constantin, Halangescu (European Scientific Journal, ESJ, 2013)
The subject of this paper seeks to transpose the main conceptual aspects of sociological model of homo oeconomicus between the limits of dilemmas and paradoxes. Built in the way of a "snapshot" of some of the most popular views on human social evolution of this type, the paper points out contradictory "curriculum vitae" models created by economists and it is a starting point for further research that can respond fully to such interrogations: Is homo oeconomicus the representation of the total man or a caricature? Is homo oeconomicus the quintessence of true economic human behavior? The ideas advanced in this paper generate conclusions between subjectivism and objectivism positioning and argues that the identity of homo oeconomicus is dependent on adaptive human social anthropology in composition, re-composition, decomposition, association and dissociation. Evolution of the concept, the idea, the abstraction, and finally the model of homo oeconomicus and undeniable presence quota "complicates" things, and our character is more "scar", not lack of affection and impeccability.